Mothers of invention : feminist authors and experimental fiction in France and Quebec - Santoro, Miléna, 1965- (McGill-Queen's University Press, 2002)
Mothers of Invention draws together innovative works of fiction written by French and Quebec feminists in the mid-1970s. Through an analysis of the strategies adopted by Hélène Cixous, Madeleine Gagnon, Nicole Brossard, and Jeanne Hyvrard as they rework maternal and (pro)creative metaphors and play with language and conventions of genre, Miléna Santoro identifies a transatlantic community of women writers who share a subversive aesthetic that participates in, even as it transforms, the tradition of the avant-garde in twentieth-century literature.